Terrorist organizations and their ideological foundations as a security threat - Tomáš DOLEŽAL (Košická bezpečnostná revue)
The emergence of terrorist organizations represents a significant and evolving security threat to global stability. This paper examines the ideological foundations, organizational structures, and operational tactics of various terrorist groups, analyzing how these elements contribute to the persistence and expansion of their activities. It explores the ideological drivers that fuel extremism, such as political, religious, and socio-economic factors, and investigates the role of propaganda, recruitment strategies, and the use of technology in spreading extremist ideologies. The study further delves into the security implications posed by these groups, focusing on the challenges they present to national and international security frameworks. By providing a comprehensive analysis of the underlying causes and operational mechanisms of terrorist organizations, this article seeks to offer insights into the multifaceted nature of the terrorist threat and suggest potential countermeasures to mitigate its impact on global peace and security.